The Education as life skills: as costs enter art, communication and education - Rabelo, Cláudio Renato Zapalá (Farol, 2024)
A Rhizome-education starts from the excerpts and inspirations from the perspectives of Deleuze, Guattari, Certeau, Foucault, Derridà, Freire, Didi-Huberman and many Other theoretical intercessors who help us to give new meaning to the arts, communication and education in transdisciplinary, critical contexts and political. Based on the research method with everyday life, our objective is to seek protagonism, creativity and innovation in media appropriation, as forms of resistance and creation of pedagogies in networks.